(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article Uzbekistan Descriptive Art Development for Contribution added artist Orol Tansikbayev’s life and creativity the information given The artist’s creative works and their analysis. Creative in his works, the landscape genre about creative his works commonly illuminated given